2018
DOI: 10.1159/000491565
|View full text |Cite|
|
Sign up to set email alerts
|

Lentivirus-Mediated Silencing of Src Homology 2 Domain-Containing Protein Tyrosine Phosphatase 2 Inhibits Release of Inflammatory Cytokines and Apoptosis in Renal Tubular Epithelial Cells Via Inhibition of the TLR4/NF-kB Pathway in Renal Ischemia-Reperfusion Injury

Abstract: Background/Aims: Renal reperfusion injury occurs after the blood flow to the ischemic kidney is re-established under various clinical conditions, such as organ transplantation, renal artery stenosis, embolic disease, and the repair of descending aortic. The current study aims to explore the effects of src homology 2 domain-containing protein tyrosine phosphatase 2 (SHP-2) on the release of inflammatory cytokines and the apoptosis of renal tubular epithelial cells by regulating the TLR4/NF-κB signaling pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…SHP2 knockout in myeloid cells protected the kidneys from inflammatory damage and prevented renal fibrosis after unilateral ureter obstruction [130]. SHP2 deficiency also had a protective effect in renal ischemia-reperfusion [131]. SHP2 is assumed to have an additional role as an antagonist of TBK1 beyond its phosphatase activity [104,105].…”
Section: Bcl3mentioning
confidence: 99%
“…SHP2 knockout in myeloid cells protected the kidneys from inflammatory damage and prevented renal fibrosis after unilateral ureter obstruction [130]. SHP2 deficiency also had a protective effect in renal ischemia-reperfusion [131]. SHP2 is assumed to have an additional role as an antagonist of TBK1 beyond its phosphatase activity [104,105].…”
Section: Bcl3mentioning
confidence: 99%
“…Previous studies have revealed that select inflammatory signaling pathways are involved in the processes driving AKI. Teng et al showed that the lentivirus-mediated silencing of SHP2 improved I/R-induced AKI via inhibition of the TLR4/NF-kB Pathway (Teng et al 2018 ). Chen et al revealed that the PHPS1 exerted a protective effect against atherosclerosis via suppression of the SHP2:ERK pathway activation (Chen et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that SHP1, but not SHP2, reduces PD-L1-dependent regulation of T regulatory lymphocyte (Treg) function and is associated with resolution of shock- and sepsis-induced lung injury (Tang et al 2015 ). Additionally, previous research has demonstrated that SHP2 deficiency may have a protective effect in experimental renal (Hsu et al 2017 ; Teng et al 2018 ; Verma et al 2016 ) and cardiovascular (Chen et al 2018 ) injury. Thus, it appears that SHP2 activation may have differential effects depending on the location of action.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that select inflammatory signaling pathways are involved in the processes driving AKI. Teng et al (Teng, et al 2018) showed that the lentivirus-mediated silencing of SHP2 improved I/R-AKI via inhibition of the TLR4/NF-kB Pathway. Chen et al revealed that the SHP2 inhibitor PHPS1 exerted a protective effect against atherosclerosis via suppression of the SHP2:ERK pathway activation.…”
Section: Many Animal Models Have Been Used To Investigate the Developmentioning
confidence: 99%
“…We recently reported that SHP1, but not SHP2, negatively modulated PD-L1 dependent regulation of T regulatory lymphocyte (Treg) function and in so doing contributed to resolving shock/sepsis-induced lung injury (Tang et al 2015). At the same time, some studies have revealed that SHP2 deficiency may have a protective effect in experimental renal (Hsu et al 2017, Teng et al 2018, Verma et al 2016) and cardiovascular (Chen et al 2018) conditions. Thus, SHP2 activation may play distinct roles in different organs.…”
Section: Introductionmentioning
confidence: 99%